2021
DOI: 10.3390/cancers13215377
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in the Diagnosis of Testicular Germ Cell Tumors: A National Cancer Registry Study in Austria

Abstract: We conducted a retrospective National Cancer Registry study in Austria to assess a possible seasonal variation in the clinical diagnosis of testicular germ cell tumors (TGCT). In total, 3615 testicular cancer diagnoses were identified during an 11-year period from 2008 to 2018. Rate ratios for the monthly number of TGCT diagnoses, as well as of seasons and half-years, were assessed using a quasi-Poisson model. We identified, for the first time, a statistically significant seasonal trend (p < 0.001) in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
1
3
1
Order By: Relevance
“…In conclusion, we found barely any seasonal variation of the incidence of testicular cancer. Our results are in conflict with a recent Austrian study [6]. However, as the present evaluation involves an almost ten-fold larger patient population than the Austrian study, the weight of evidence of the present investigation appears greater.…”
Section: Plos Onecontrasting
confidence: 99%
See 3 more Smart Citations
“…In conclusion, we found barely any seasonal variation of the incidence of testicular cancer. Our results are in conflict with a recent Austrian study [6]. However, as the present evaluation involves an almost ten-fold larger patient population than the Austrian study, the weight of evidence of the present investigation appears greater.…”
Section: Plos Onecontrasting
confidence: 99%
“…The over-all annual incidence rate of GCT in Germany [15], the higher incidence of seminoma compared to that of nonseminoma [16,17], and the PLOS ONE much higher incidence of GCT in younger than in older ages are in line with previous publications [7,17,18]. However, our data are at odds with the results of the Austrian group who reported significant increases of the GCT incidence in autumn and winter months [6]. Yet, a closer look at the data of the Austrian study reveals that the difference between the summer and winter period was restricted to the histologic subgroup of seminoma and particularly to cases with localized disease.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Seasonal variation in cancer incidence was previously described for melanoma, prostate cancer and thyroid cancer based on research released by the Swedish Cancer Registry [ 13 ]. We recently observed that the registered incidence of TGCT in Austria also has a strong seasonal pattern, with a reduction in the tumor incidence during the summer months and an increase during the winter months [ 14 ]. We hypothesize that these temporal patterns may reflect complex biological processes affecting the likelihood of TGCT carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%